A new flexural-tensegrity bow. (October 2021) - Boni, Claudio; Royer-Carfagni, Gianni
Highlights: The segmental design concept of flexural tensegrity is applied to the optimization of the bow. The bending capacity depends upon the kinematics of the contact surface between segments. The new bow is theoretically analyzed, prototyped and tested, in static and dynamic conditions. Energetic efficiency, arrow exit speed, shooting accuracy, archer's comfort are considered. This bow can outperform classical bows. Segmental construction allows folding and packaging. Abstract: The bow is a simple machine now representing a paradigmatic example for demonstrating the applicability of the structural concept of flexural tensegrity, as chains of segments in unilateral contact coupled by unbonded prestressing tendons. The nonlinear and nonlocal constitutive laws for bending are dictated by the tendon prestress and, explicitly, by the shape of the contact surfaces between segments. Optimization requires functionally graded elastic properties fulfilling different objective functions, in terms of energetic efficiency, arrow exit speed, shooting accuracy, archer's comfort. An innovative non-recurve composite bow, called FlexTen bow, is theoretically analyzed, prototyped and tested, under static and dynamic conditions. Two different designs are considered, identical except for the shape of the contact surfaces between segments, so that the lever arm of the internal couple is either a linear or a sub-linear function of relative rotation. The FlexTen bow with sub-linear behavior outperforms classical bows, but the advantages, yet to be fully appreciated, also consist in the modular construction and the possibility of packaging.